Frequency characteristics of a viscoelastic graphene nanoplatelet–reinforced composite circular microplate. (January 2021) - Ghabussi, Aria; Habibi, Mostafa; NoormohammadiArani, Omid; Shavalipour, Aghil; Moayedi, Hossein; Safarpour, Hamed
This is the first research on the frequency analysis of a graphene nanoplatelet composite circular microplate in the framework of a numerical-based generalized differential quadrature method. Stresses and strains are obtained using the higher order shear deformation theory. The microstructure is surrounded by a viscoelastic foundation. Rule of the mixture is used to obtain varying mass density and Poisson's ratio, whereas the module of elasticity is computed by a modified Halpin–Tsai model. Governing equations and boundary conditions of the graphene nanoplatelet composite circular microplate are obtained by implementing Hamilton's principle. The results show that outer to inner radius ratio( R o / R i ), ratios of length scale and nonlocal to thickness ( l / h andμ / h ), and graphene nanoplatelet weight fraction( g GPL ) have significant influence on the frequency characteristics of the graphene nanoplatelet composite circular microplate. Another necessary consequence is that by increasing the value ofR o / R i, the distribution of the displacement field extends from radial to tangent direction, especially in the lower mode numbers; this phenomenon appears much more remarkable. A useful suggestion of this research is that for designing the graphene nanoplatelet composite circular microplate at a low value ofR o / R i, g GPL andR o / R i should be given more attention, simultaneously. An interesting result which has come down from the article is that the effect ofR o / R i on the dimensionless frequency of the structure is really dependent on the value of C d .